THERMAL SCREENS ON THE BASIS OF FIBROUS MATERIALS INCLUDING WATER SOLUTIONS - H. A. Abdulkaber (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Fibrous materials including water solutions are explored. Possibility of their use in constructions of thermal screens for decrease thermal perceptibility of the mobile land objects is shown.